ANALISIS PERBANDINGAN SISTEM SENJATA MULTI-LAYERED UNTUK PERTAHANAN UDARA KOTA DALAM PERANG MODERN - Iman, Khoerozadi Faizal; Robertus Heru Triharjanto; Heri Budi Wibowo; Yayat Ruyat (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
In the era of modern warfare, urban defense is a very important aspect to maintain the security and stability of a country. Because modern war is a non-military war in which developed countries and foreign countries try to destroy a country through ideological, political, social, cultural and security defense. To protect the territory with effective air defense, it takes a strong and sophisticated defense resources with a reliable range of surveillance and agility to destroy any effort that threatens the security and sovereignty of the country. To achieve the objective of building a more efficient air defense system and functioning alongside other air defense platforms, new ideas and thinking are needed for program planning and the requirements of medium-range missile systems when building an air defense system. The research method used in this research is descriptive qualitative through a literature study. In the literature review, it is necessary to conduct a thorough search to ensure that the literature sources used are truly relevant to the research topic and a comparative analysis approach is used. In the realm of analyzing layered weapon systems, such as Hisar O, Hisar A, Korkut Gun System, Iron Dome, and NASAMS, it becomes imperative to delve into the comparative analysis and interpret the implications of their similarities and differences. Hisar O, a sophisticated air defense system, showcases advanced capabilities designed to counter aerial threats. Its cutting-edge technology and robust infrastructure provide a formidable defense mechanism. On the other hand, Hisar A, another component of the layered defense, excels in short-range air defense, ensuring effective protection against low-altitude aerial targets. Korkut Gun System, presents a unique blend of artillery and air defense capabilities. Its adaptable nature allows it to provide ground forces with enhanced protection against a wide range of threats. Iron Dome system has gained international recognition for its exceptional performance in countering short-range rocket threats. This innovative system incorporates advanced tracking and interception technologies, enabling it to neutralize incoming projectiles with a high success rate. NASAMS (Nationals Advanced Surface-to-Air Missile System) stands out as a versatile air defense solution. Its state-of-the-art radar and missile technologies ensure reliable protection against a variety of airborne threats, including aircraft, helicopters, and unmanned aerial vehicles (UAVs). Now, let's delve into the implications of these comparative analyses for Indonesia. By understanding the strengths and weaknesses of each system, Indonesian defense strategists can make informed decisions regarding their defense capabilities. This analysis assists in identifying potential gaps in the country's air defense network and formulating strategies to address them effectively. In conclusion, through a comparative analysis of layered weapon systems such as Hisar O, Hisar A, Korkut Gun System, Iron Dome, and NASAMS, we gain valuable insights into their capabilities and implications. evaluating differences and similarities, can help Indonesian defense planners make informed decisions to strengthen city air defense systems in the modern warfare.